Effects of antipsychotic drugs and potassium channel modulators on spectral properties of local field potentials in mouse hippocampus and pre-frontal cortex. (15th June 2021) - Sun, Dechuan; Kermani, Mojtaba; Hudson, Matthew; He, Xin; Unnithan, Ranjith Rajasekharan; French, Chris
Abstract: Local field potentials (LFPs) recorded intracranially display a range of location-specific oscillatory spectra which have been related to cognitive processes. Although the mechanisms producing LFPs are not completely understood, it is likely that voltage-gated ion channels which produce action potentials and patterned discharges play a significant role. It is also known that antipsychotic drugs (APDs) affect LFP spectra and a direct inhibitory effect on voltage-gated potassium channels has been reported. Additionally, voltage-gated potassium channels have been implicated in the pathophysiology of schizophrenia, a disorder for which APDs are primary therapies. In this study we sought to: i) better characterise the effects of two APDs on LFPs spectra and connectivity measures and ii) examine the effects of potassium channel modulators on LFPs and potential overlap of effects with APDs. Intracranial electrodes were implanted in hippocampus (HIP) and pre-frontal cortex (PFC) of C57BL/6J mice; power spectra, coherence and phase-amplitude cross-frequency coupling were measured. Drugs tested were APDs haloperidol and clozapine as well as voltage-gated potassium channel modulators (KVMs) 4-aminopyridine (4-AP), tetraethylammonium, retigabine and E−4031. Both APDs and KVMs significantly reduced gamma power except 4-AP, which conversely increased gamma power. Clozapine and retigabine additionally reduced gamma coherence between HIP and PFC, while 4-AP demonstrated the opposite effect. Phase-amplitude coupling between theta and gamma oscillations in HIP was significantly reduced by the administration of haloperidol and retigabine. These results provide previously undescribed effects of APDs on LFP properties and demonstrate novel modulation of LFP characteristics by KVMs that intriguingly overlap with the APD effects. Highlights: Haloperidol and clozapine reduce gamma power in HIP and PFC. TEA, retigabine and E−4031 reduce gamma power in HIP and PFC. Clozapine and retigabine reduce gamma coherence between HIP and PFC. 4-AP increases gamma power and coherence between HIP and PFC. Haloperidol and retigabine reduce hippocampal cross-frequency coupling.